(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research dealt with the study and analysis of mixed working systems by employing simulation experiments in Estimation the reliability function of the mixed system by using sample sizes and values of different hypothetical parameters on the assumption that the life time of the compounds are distributed Pareto distribution and Rayleigh distribution. The comparison criterion was adopted on the statistical scale (average of integral error squares) in order to determine the priority of each method through the results that were reached